High-quality permanent draft genome sequence of Rhizobium leguminosarum bv. viciae strain GB30; an effective microsymbiont of Pisum sativum growing in Poland. Issue 1 (December 2015) - Mazur, Andrzej; De Meyer, Sofie; Tian, Rui; Wielbo, Jerzy; Zebracki, Kamil; Seshadri, Rekha; Reddy, TBK; Markowitz, Victor; Ivanova, Natalia; Pati, Amrita; Woyke, Tanja; Kyrpides, Nikos; et al.
Abstract Rhizobium leguminosarum bv.viciae GB30 is an aerobic, motile, Gram-negative, non-spore-forming rod that can exist as a soil saprophyte or as a legume microsymbiont ofPisum sativum . GB30 was isolated in Poland from a nodule recovered from the roots ofPisum sativum growing at Janow. GB30 is also an effective microsymbiont of the annual forage legumes vetch and pea. Here we describe the features ofR. leguminosarum bv.viciae strain GB30, together with sequence and annotation. The 7, 468, 464 bp high-quality permanent draft genome is arranged in 78 scaffolds of 78 contigs containing 7, 227 protein-coding genes and 75 RNA-only encoding genes, and is part of the GEBA-RNB project proposal.